2014
DOI: 10.1007/s00403-014-1485-3
|View full text |Cite
|
Sign up to set email alerts
|

Calcipotriol counteracts betamethasone-induced decrease in extracellular matrix components related to skin atrophy

Abstract: The calcipotriol/betamethasone dipropionate fixed-combination gel is widely used for topical treatment of psoriasis vulgaris. It has been hypothesized that calcipotriol counteracts glucocorticoid-induced skin atrophy which is associated with changes in the extracellular matrix (ECM). To elucidate the combined effects of calcipotriol and betamethasone on key ECM components, a comparative study to the respective mono-treatments was carried out. The effect on collagen I synthesis, matrix metalloproteinase (MMP) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
39
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 34 publications
3
39
0
4
Order By: Relevance
“…Skin aging/photoaging is associated with the loss of structural collagen, co-regulated HSP-47, and solar elastosis from stimulation of elastin and elastases [1,3,12,14,16]. Vitamin D stimulates collagen expression and inhibits elastin expression in dermal fibroblasts [35][36][37]. We herein report that vitamin D stimulates the expression of type I collagen, transcriptionally, in non-irradiated and UVA-radiated fibroblasts, though not in UVB-radiated fibroblasts.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Skin aging/photoaging is associated with the loss of structural collagen, co-regulated HSP-47, and solar elastosis from stimulation of elastin and elastases [1,3,12,14,16]. Vitamin D stimulates collagen expression and inhibits elastin expression in dermal fibroblasts [35][36][37]. We herein report that vitamin D stimulates the expression of type I collagen, transcriptionally, in non-irradiated and UVA-radiated fibroblasts, though not in UVB-radiated fibroblasts.…”
Section: Discussionmentioning
confidence: 74%
“…The UV radiation is the predominant environmental factor that accelerates skin aging. The regulatory properties of 1α, 25dihydroxyvitamin D3 (vitamin D) include endocrine, ECM regulation, cell differentiation, photoprotection, and anti-inflammation [34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been observed that the combined pharmacological treatment improves the patients' adherence to therapy, since in a single application they can use both drugs, minimizing the side effects of cortisone (Patel, Felix, Reimer, & Feldman, ). It is in fact believed that calcipotriol is able to counteract the atrogenic effect of the corticosteroid through a mechanism of modulation of the extracellular matrix (Norsgaard et al, ). More and more recent studies are aimed at improving the penetration of the molecules contained in the foam, favoring effectiveness and reducing health care expense (Frieder, Kivelevitch, & Menter, ).…”
Section: Discussionmentioning
confidence: 99%